Risk of disability among adult leprosy cases and determinants of delay in diagnosis in five states of India: A case-control study. - Govindarajulu Srinivas; Thirumugam Muthuvel; Vivek Lal; Kanagasabapathy Vaikundanathan; Eva-Maria Schwie; Christa Kasang (Public Library of Science (PLoS), 2019)
INTRODUCTION:A high proportion of grade 2 disability (visible deformity) is indicative of delay in detection of leprosy and leprosy is one of the major causes of preventable disability. We conducted this study to determine the risk factors associated with disability (G2D and G1D) among adult new leprosy cases and to measure their strength of association. METHODS:A multi-centric case-control study was undertaken in five states of India i.e. Andhra Pradesh, Delhi, Gujarat, Maharashtra and West Bengal). Among new adult patients, cases were defined as those with disability (G2D and G1D) at the time of diagnosis and controls were defined as those without any disability (G0D). Delays were quantified based on patient recall across a timeline. Patient delay defined as the time period between first noticed symptom by the patient and the first visit to any health care provider (HCP); HCP delay defined as the time period between patient's first visit to any HCP and the confirmation of diagnosis of leprosy; and total delay defined as the sum of both patient and HCP delays. RESULTS:A total of 1400 new leprosy patients (700 G2D/G1D and 700 G0D) across five states were interviewed. Among G2D/G1D, the median patient delay was 8 months compared with 4 months among G0D. The median HCP delay was 2 months for G2D/G1D and 1 month for G0D. The median total delay was 14 months for G2D/G1D and 6.2 months for G0D; observed median difference between groups was statistically significant (p<0.001). When patient delay was more than 3 months, odds of G2D/G1D at diagnosis were 1.6 times higher compared to when patient delay was less than 3 months. When the HCP delay was more than one month, the odds of G2D/G1D were 1.4 times higher compared to when the HCP delay was less than one month. When the patient had multi-bacillary type leprosy the odds of G2D/G1D at the time of diagnosis was nine times higher compared to pauci-bacillary type leprosy. CONCLUSION:Patient delay is the major reason for risk of disability (G2D/G1D) among adult leprosy patients. A patient delay of more than 3 months from the notice of first symptom is a significant indicator for the disabilities among adult leprosy patients. Early case detection campaigns like active surveys in endemic spots should be done periodically as this can reduce delays and promote early diagnosis. Additionally, the program should lay greater emphasis on raising community awareness regarding the disease. Also, health care provider delay of more than 1 month have been significant risk factors for disability among adult leprosy cases. Hence, periodical capacitation of all HCPs including private practitioners would significantly contribute to reduce diagnostic delay and promote timely referral and early detection.